Effect of CMC Molecular Weight on Acid‐Induced Gelation of Heated WPI‐CMC Soluble Complex. Issue 2 (11th January 2016) - Huan, Yan; Zhang, Sha; Vardhanabhuti, Bongkosh
Abstract: Acid‐induced gelation properties of heated whey protein isolate (WPI) and carboxymethylcellulose (CMC) soluble complex were investigated as a function of CMC molecular weight (270, 680, and 750 kDa) and concentrations (0% to 0.125%). Heated WPI‐CMC soluble complex with 6% protein was made by heating biopolymers together at pH 7.0 and 85 °C for 30 min and diluted to 5% protein before acid‐induced gelation. Acid‐induced gel formed from heated WPI‐CMC complexes exhibited increased hardness and decreased water holding capacity with increasing CMC concentrations but gel strength decreased at higher CMC content. The highest gel strength was observed with CMC 750 k at 0.05%. Gels with low CMC concentration showed homogenous microstructure which was independent of CMC molecular weight, while increasing CMC concentration led to microphase separation with higher CMC molecular weight showing more extensive phase separation. When heated WPI‐CMC complexes were prepared at 9% protein the acid gels showed improved gel hardness and water holding capacity, which was supported by the more interconnected protein network with less porosity when compared to complexes heated at 6% protein. It is concluded that protein concentration and biopolymer ratio during complex formation are the major factors affecting gel properties while the effect of CMC molecular weight was less significant.